2018
DOI: 10.21278/tof.41403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Treatment on Corrosion Resistance of Austenitic Biomaterial

Abstract: SummaryThis paper focuses on the effect of surface treatment (grinding, electrochemical polishing) on the corrosion resistance of AISI 316L, a Cr-Ni-Mo low-carbon austenitic surgical stainless steel, in a physiological solution at the temperature of 37 °C. The influence of a surface defect and of sensitization by heat treatment on the corrosion behaviour of electrochemically polished surface is also studied. The evaluation is based on the results of cyclic potentiodynamic polarization tests and on the microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…Its concentration was higher in C-B than in the other formulations. Fluorides were only present in SALMO, and the concentration of 0.11 mg/dm 3 NaF was low in comparison with the concentration of these anions in the literature, e.g., 500 mg/dm 3 NaF and 5000 mg/dm 3 NaF, 21 1000 mg/dm 3 NaF, 4 and 2000 mg/dm 3 NaF. 22 The concentration of chlorides is almost equal in all the solutions (29.8 × 10 −3 M in D, 28.1 × 10 −3 M in CB, and 25.3 × 10 −3 M in SALMO).…”
Section: ■ Experimental Sectionmentioning
confidence: 60%
See 1 more Smart Citation
“…Its concentration was higher in C-B than in the other formulations. Fluorides were only present in SALMO, and the concentration of 0.11 mg/dm 3 NaF was low in comparison with the concentration of these anions in the literature, e.g., 500 mg/dm 3 NaF and 5000 mg/dm 3 NaF, 21 1000 mg/dm 3 NaF, 4 and 2000 mg/dm 3 NaF. 22 The concentration of chlorides is almost equal in all the solutions (29.8 × 10 −3 M in D, 28.1 × 10 −3 M in CB, and 25.3 × 10 −3 M in SALMO).…”
Section: ■ Experimental Sectionmentioning
confidence: 60%
“…XPS analyses showed that the passive film formed on the stainless steel was mainly composed of chromium oxide and iron oxide, and in the presence of fluoride, a slight increase in the intensity of the metallic components was observed. 4 Zatkali ́kováet al 21 reported that the addition of fluoride ions (0.5 g/dm 3 NaF and 5 g/dm 3 NaF) to a chloride-bearing solution (0.9% NaCl) led to an increase of the pitting potential, thus indicating that fluoride ions inhibit pitting corrosion in a neutral chloride solution. Prolonged immersion tests (42 days) showed local pitting corrosion in the solutions both with and without fluorides.…”
Section: Possible Applications Of Din 14456 Stainless Steel Inmentioning
confidence: 99%
“…[14] The influence of surface roughness of SS and other metals and alloys on their resistance to pitting corrosion has been considered in a large number of papers. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The roughness test results presented in these papers are often contradictory. Ezuber et al [15] have shown that resistance to pitting corrosion increases with decreasing surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The size and amount of Al5FeSi also contribute to the formation of solidification defects, such as porosity and hot tearing (Puncreobutr et al, 2014). The commonly used assessment of such dimensions are quantitative image analysis (Vaško, 2016;Bilewicz et al, 2013;Belan, 2014, Zatkalíková, 2017. These methods provide numerical and accurate values of microstructural features.…”
Section: Introductionmentioning
confidence: 99%